2011
DOI: 10.1093/bja/aer299
|View full text |Cite
|
Sign up to set email alerts
|

Annexin 1 exerts anti-nociceptive effects after peripheral inflammatory pain through formyl-peptide-receptor-like 1 in rat dorsal root ganglion

Abstract: Endogenous ANXA1 expression at the DRG level is involved in CFA-induced inflammatory pain, and i.t. ANXA1 20 µg µl(-1) produces its anti-nociceptive effect through FPR2/ALX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 29 publications
(26 reference statements)
3
38
1
1
Order By: Relevance
“…This effect was dampened by Boc-1, demonstrating that the activation of nFPRs mediated this process. Moreover, in previous in vivo experiments, our lab showed that Ac2-26 could attenuate neuropathic pain by interacting with Fpr2 (Pei et al, 2011), providing additional evidence that nFPRs could be a potent candidate for the treatment of inflammatory neuropathies.…”
Section: Discussionmentioning
confidence: 79%
“…This effect was dampened by Boc-1, demonstrating that the activation of nFPRs mediated this process. Moreover, in previous in vivo experiments, our lab showed that Ac2-26 could attenuate neuropathic pain by interacting with Fpr2 (Pei et al, 2011), providing additional evidence that nFPRs could be a potent candidate for the treatment of inflammatory neuropathies.…”
Section: Discussionmentioning
confidence: 79%
“…Control sections were incubated without the primary antibody, and no staining was observed. Double immunofluorescence staining of ganglion sections was described previously [32]. Mounted NG sections were thawed at room temperature, and indirect immunofluorescence was used to detect P2X1, P2X2, P2X3, and P2X4.…”
Section: Methodsmentioning
confidence: 99%
“…FPRs have homologs in fish and rodents [13,14]. For example, Fpr2, a homolog of human FPR2, is localized in rat satellite glial cells and neurons of dorsal root ganglions [15]. Expression of Fpr1 and Fpr2 was also reported in rat neuronal stem cells [16].…”
Section: Introductionmentioning
confidence: 99%